2020
DOI: 10.1088/1402-4896/ab80e6
|View full text |Cite
|
Sign up to set email alerts
|

Quantum particles in a moving potential

Abstract: We study the behavior of a quantum particle, trapped in localized potential, when the trapping potential starts suddenly to move with constant velocity. In one dimension we have reproduced the results obtained by Granot and Marchewka, Ref.[1], for an attractive delta function, using an approach based on a spectral decomposition, rather than on the propagator. We have also considered the cases of Pöschl-Teller and simple harmonic oscillator potentials (in one dimension) and to the hydrogen atom (in three dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Among these perturbations, we can presuppose the scenario in which MWSs are dragged by mobile potentials with constant velocity. Adhikari et al [19] and Malomed et al [20] observed gap soliton stabilities in superfluids Fermi gases (SFG) trapped in mobile optical lattices, Muruganandam et al [21] observed gap solitons in a dipolar BEC trapped in mobile optical lattices and, recently, Ahumada‐Centeno et al [22] studied the behavior of quantum particles confined to mobile potentials. Anyway, BECs subject to these configurations have very interesting properties that can be applied in several situations, such as solitons propagation in optical fibers [23], ultrashort optical pulses in fiber couplers [24] and stability of solitary waves in Kerr media [25].…”
Section: Introductionmentioning
confidence: 99%
“…Among these perturbations, we can presuppose the scenario in which MWSs are dragged by mobile potentials with constant velocity. Adhikari et al [19] and Malomed et al [20] observed gap soliton stabilities in superfluids Fermi gases (SFG) trapped in mobile optical lattices, Muruganandam et al [21] observed gap solitons in a dipolar BEC trapped in mobile optical lattices and, recently, Ahumada‐Centeno et al [22] studied the behavior of quantum particles confined to mobile potentials. Anyway, BECs subject to these configurations have very interesting properties that can be applied in several situations, such as solitons propagation in optical fibers [23], ultrashort optical pulses in fiber couplers [24] and stability of solitary waves in Kerr media [25].…”
Section: Introductionmentioning
confidence: 99%
“…[9] At finite temperatures, therefore, the moiré potential is dynamic and the charge carriers reside in a highly mobile trapping potential. The behaviour of a quantum particle in such a time-dependent trapping potential is an interesting problem [10][11][12] with applications to quantum transients [13], transport of small particles using scanning tunnelling microscopy or optical tweezers, and charge transport [14].…”
mentioning
confidence: 99%
“…At finite temperatures, therefore the moiré potential is dynamic, and the charge carriers reside in a highly mobile trapping potential. The behavior of a quantum particle in such a time-dependent trapping potential is an interesting problem with applications to quantum transients, transport of small particles using scanning tunneling microscopy or optical tweezers, and charge transport …”
mentioning
confidence: 99%